ENDORSING SENSE OF IDENTITY FOR COLLEGE STUDENTS’ ENGLISH LANGUAGE PERFORMANCE - Yuehong Wei; Li Zhang (English Review: Journal of English Education, 2016)
Triggered by the lack of students’ sense of identity in English regular class effects their language achievement, this research aimed at developing a kind of teaching mode for building students’ sense of identity with a series of teaching activities. Targeted at 55 non-English major students for one semester, the experiment was to explain the effectiveness of this kind of mode in endorsing student’s sense of identity. Here, the researcher used teaching observation and students’ feedback to collect the data. It revealed that the kind of mode can help improve students’ sense of identity, intrigue their interest, and improve their English learning efficiency.Keywords: sense of identity, college English, regular class, English class, teaching research